Model Rekayasa Informasi Penerimaan Peserta Didik Baru (PPDB) Berbasis Web (Studi Kasus Sekolah Menengah Atas Mardi Waluya Cibinong) - Komul, Theodora Maria Putri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The paradigm for how society seeks and obtains information has changed as a result of the rapid advancement of information technology in recent years. Newspapers, audiovisual materials, and electronic sources are no longer the only sources available; other sources of information, such as the internet, are now included. Websites are an efficient and successful way to communicate information. The management of a school benefits greatly from online admission of new pupils, which makes it simpler to conduct monitoring and evaluation in an effort to raise the standard of instruction. Database-supporting information technology infrastructure is required to raise the caliber of education. Many secondary schools still manage new student admissions data in an unintegrated manner, which prevents them from providing timely, accurate, and comprehensive information about education, enhancing teachers' proficiency in the area of information technology, as well as providing parents and children with accurate and superior quality information. Students and the general public can readily access the web-based information system for SMA Mardi Waluya Cibinong to obtain information about the school